Implementasi Sistem E-Rapor guna mengetahui Perkembangan Anak berbasis Moodle Studi Kasus Paud Azizah - Afifa Diniputri; Suhendi Suhendi (Jurnal Informatika Terpadu, 2021)
Paud Azizah is one of the schools that, as the Standard Curriculum utilizes the BCCT (Beyond Circle and Center Time) process, Paud Azizah uses this method for synergistic learning while playing or playing while learning with learning strategies. The teacher will write down the activities carried out by the students and their progress in school through a connecting book that will be provided as a result of the report by the parents of the students. But not all of each student's parents read the notes in the connecting book since the parents are busy themselves. This study developed a Moodle-based e-report system to resolve this problem. This method requires teachers to generate information on child development and report cards for one semester to assess teaching and learning activities. But not all of each student's parents read the notes in the connecting book since the parents are busy themselves. This study developed a Moodle-based e-report card system to resolve this problem. This method requires teachers to generate information on student development and report for one semester as an evaluation of teaching and learning activities. In Paud Azizah, Moodle's function as a reporting system for child development is to help easily access communication between teachers and parents or guardians without barriers that make it difficult for both parties. By going through several testing phases, the author is implementing the application to develop the Moodle system at Paud Azizah. Beginning with the identification of problems in preliminary studies and literature, systems analysis in the form of data and information, system design in the form of mockup designs, systems implementation, and testing systems that apply the UAT method by creating questionnaires as a result of the implementation process for teachers and guardians of students at Paud Azizah as a result of the implementation process.